POTENCY ESTIMATION ON OXYGEN PRODUCTION OF TREE STAGE VEGETATION AT THE HIMBA KAHUI URBAN FOREST IN PALANGKA RAYA - Ludang, Yetrie; Junaedi, Ajun; Putir, Patricia Erosa (Acta Scientiae et Intellectus, 2024)
The research aims to (a) know the composition and structure of tree stage vegetation, (b) calculate the estimation of biomass stock, carbon and CO2 sequestration on the tree stage vegetation, (c) calculate the estimation of O2 produced from the tree stage vegetation, (d) analyze O2 supply needed by Palangka Raya residents related to the number of O2 produced by the tree stage vegetation. The research was conducted on Himba Kahui Urban Forest in Palangka Raya, located administratively at Petuk Katimpun, Bukit Tunggal and Palangka Sub-District on Jekan Raya District and also at Rungan Sub-District, Pahandut District. The object to study was the tree stage vegetation (stem diameter ≥ 20 cm), meanwhile the measurement estimation on biomass stock, carbon, and CO2 sequestration and O2 potential was worked with non destructive method using equation by Krisnawati, et. al. (2012), SNI 7724 (2011) and IPCC (2006). The result of this research indicates the number of the tree stage vegetation variants from 13 families and the dominance of Perupuk tree variant (Lophopetalum multinervium) with Important Value Index (IVI) at 36.65%. The highest vegetation density was dominated by diameter class of 25-29 cm (horizontal structure) and height class of 13-15 m dominated by vertical structure. The biomass stock, CO2 sequestration and O2 potential production of tree stage vegetation is 39.58 ton/ha, 18.60 tonC/ha, 68.28 tonCO2/ha and 49.84 tonO2/ha respectively. The need of O2 supply for Palangka Raya residents in 2014 was 217.82 tonO2/day or 217.820 kgO2/day and can be supplied by the O2 produced by the tree stage vegetation at Himba Kahui City Forest in Kota Palangka Raya.